Sternal manubrium chondrosarcoma. Case report and literature review. - González, Daniel; Vega, Alvaro; Torres, Marcos; di Leoni, Francisco (Cirugía del Uruguay, 2006)
The chondrosarcoma is the most frequent malignant tumor of sternum, and incidence on manubrium is low. There was one case of this particular topography in a 56-years- old female patient in the Florida Hospital, with pain and tumor clinical presentation. A thoracic CAT scan showed tumoration of the manubrium sternum with bone destruction and this diagnosis was confirmed through biopsy and immunohistochemical techniques wich served to establish it as a poorly differentiated chondrosarcoma. Tumor resection was made with sufficient margin, and it was possible to reconstruct the parietal gap with polipropylene mesh. Survival of disease was 23 months.